Uji Validitas Eosinopenia Pada Pasien Sepsis Berdasarkan Kriteria Konsensus Sepsis-3 - Adrian Suhendra; Ida Parwati; Adhi K Sugianli (Universitas Kristen Maranatha, 2023)
Sepsis remains a major global healthcare problem, indicate as most frequently cause of morbidity and mortality worldwide. The last consensus of sepsis in 2016 defined sepsis as life threatening organ dysfunction caused by a dysregulated host response to infection. Dysfunction of organs can be represented by Sequential [Sepsis-Related] Organ Failure Assessment (SOFA) score. Score2 points or more consequent to the infection. Nowadays, there is ideal biomarkers of sepsis such as procalcitonin (PCT). However, the use of that markers in developing countries are hardly accessible. Eosinopenia is an prepossess biomarker because eosinophil count is always measured in daily practice and considered as a forgotten marker. The study purpose is to determine the validity of absolute eosinopenia in bacterial sepsis patients. This study is a descriptive observational study, collecting 118 patient’s medical record data from the past, diagnosed as sepsis using consensus criteria of Sepsis-3 between January 1st 2018–December 31st 2019. Eosinopenia validity test in sepsis patients showed 92.7% specificity and 71.4% sensitivity. This study also showed significant differences of absolute eosinophil count between positive sepsis patients and negative group with p value <0.001. Eosinopenia had high specificity so it could be used as a marker of diagnostic in septic patients.